Prevalence of Gastrointestinal Parasitism in Dairy Cattle of Western Maharashtra - Kalidas Tidke, Pohandas; Dhanaji Pawar, Prashant; Balaji Kendre, Satyamurthi; Ambaji Ambore, Balaji; Ramrao Shelar, Raju (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study aimed to assess the prevalence of gastrointestinal (GI) parasitic infections in dairy cattle across seven districts of Western  Maharashtra. A total of 1088 feacal samples were examined by using quantitative and qualitative methods. Overall prevalence of GI  parasitic infections was 75.00% (816/1088) along with significant variation across districts, with the highest prevalence in Ahilyanagar  district (83.50%) and the lowest in Satara district (71.21%). Dual infections (34.28%) were more common than single (32.17%) and  multiple infections (8.54%). Adults showed a higher prevalence (77.78%) as compared to heifers (62.50%) and young ones (58.82%).  Seasonal analysis indicated higher prevalence during the monsoon season (82.67%) than in winter season (71.33%)
Keywords: Dairy cattle; Gastrointestinal parasitic infections; Maharashtra; Prevalence